Corrosion and Wear Rate Analysis of SS304 Stainless Steel with Composite Coating Variations: Aluminum/Silicon Carbide/Epoxy and Titanium Dioxide/Silicon Carbide/Epoxy - Niko Ario Septian; Hendrix Noviyanto Firmansyah; Kriswanto; Safriana, Eni (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
The palm oil industry presents significant challenges to material durability due to its corrosive and abrasive environment, particularly affecting components such as screw conveyors made from SS304 stainless steel. This study aims to analyze the influence of composite coating variations based on epoxy resin with the addition of aluminum (Al), silicon carbide (SiC), and titanium dioxide (TiO₂) on the corrosion and wear rates of SS304 in an H₂SO₄ medium. The methods employed include corrosion testing using the weight loss method in accordance with ASTM G31-72, and wear testing using the Ogoshi method following ASTM G99. Four specimen variations were evaluated: uncoated (Raw), pure epoxy, epoxy–Al–SiC (A), and epoxy–TiO₂–SiC (B).The results indicate that Specimen B exhibited the best corrosion resistance, with the lowest corrosion rate of 0.00798 mm/year, while Specimen A demonstrated the highest wear resistance, with a wear rate of 0.00042 mm³/kg·m. The pure epoxy specimen showed the poorest performance in both aspects. These findings confirm that the incorporation of reinforcing particles into the epoxy matrix plays a significant role in enhancing corrosion and wear resistance, thereby contributing to extended service life and improved equipment efficiency in extreme industrial environments.